LITERATURE OF REVIEW THE INFLUENCE OF BRAND AMBASSADOR, PRODUCT KNOWLEDGE AND BRAND TRUST ON THE DECISION TO PURCHASE SOMETHINC PRODUCTS AT UNIVERSITY of BHAYANGKARA JAKARTA RAYA - Dewi Cantika Hikmah Ulkhusna (IJESM Indonesian Journal of Economics and Strategic Management, 2023)
This research is a literature review study to determinethe influence of brand ambassadors, productknowledge and brand trust on the decision topurchase. The method used in this research isquantitative with the unit of analysis being studentsat Bhayangkara University, Jakarta Raya who usesomethinc skincare products. The population in thisstudy was 1797 with a minimum research sampleusing slovin being 95 respondents. This research willuse the SPSS 25 statistical tool to process researchdata.